2017
DOI: 10.1063/1.4995407
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization of polycrystalline diamond thin film heat spreaders grown on GaN HEMTs

Abstract: Polycrystalline diamond (PCD) was grown onto high-k dielectric passivated AlGaN/GaN-on-Si high electron mobility transistor (HEMT) structures, with film thicknesses ranging from 155 to 1000 nm. Transient thermoreflectance results were combined with device thermal simulations to investigate the heat spreading benefit of the diamond layer. The observed thermal conductivity (κDia) of PCD films is one-to-two orders of magnitude lower than that of bulk PCD and exhibits a strong layer thickness dependence, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 47 publications
1
59
0
3
Order By: Relevance
“…However, its low thermal conductivity of only 2 W/cm•K at room temperature limits the use of GaN devices in high-performance regimes [12]. Thus, a great prospect to combine GaN devices with diamond thermal management layers may be achieved by the means of layer bonding or the direct growth of diamond layers on GaN heterostructures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, its low thermal conductivity of only 2 W/cm•K at room temperature limits the use of GaN devices in high-performance regimes [12]. Thus, a great prospect to combine GaN devices with diamond thermal management layers may be achieved by the means of layer bonding or the direct growth of diamond layers on GaN heterostructures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…12 [73]. Zhou et al demonstrated that polycrystalline diamond can be effectively used as the heat spreader on AlGaN/GaN HEMTs [74]. Lin et al demonstrated that an electrically insulating 2D BN nanosheet to be used for efficient heat dissipation on high-power transistors [75].…”
Section: Thermal Management Solutions For Power Electronicsmentioning
confidence: 99%
“…Several studies have shown reduced operating temperatures of GaN devices when using integrated diamond heat spreading technology [7,8,9].…”
Section: Introductionmentioning
confidence: 99%